Does marginal cost pricing of electricity affect groundwater pumping behavior of farmers? - Meenakshi, J.V.; Banerji, A.; Mukherji, Aditi; Gupta, A. (International Water Management Institute, 2012)
The purpose of the evaluation was to quantify the impact of the recent policy change in West Bengal relating to the pricing of electricity from a flat rate tariff to metered tariff. The study attempted to assess its impact on the total number of hours pumped, especially in the summer season, and its distribution across use on the pump owner?s own farm and sales to other farmers.